Optimizing Annual Cropping Patterns Using A multi-objective Approach to Maximize Income and Minimize Soil Erosion - Faqih, Nasyiin; Suripin, Suripin; Wulandari, Dyah Ari; Qomaruddin, Mochammad (International Journal of Engineering, Science and Information Technology, 2025)
This research investigates planting strategies to optimize productivity and conserve soil, focusing on potatoes and onions grown on erosion-prone land. Cross planting versus perpendicular plantings is evaluated using the MOORA (Multi-Objective Optimization Based on Ratio Analysis) method based on erosion rates, crop productivity, and economic outcomes. Meanwhile, data from six experimental contour and perpendicular planting plots are analyzed. The measurements for sediment and runoff are carried out using a dual-bucket system. After erosion calculations, the highest erosion rate was found in the contour planting of shallots at 385,65 tons/ha/year. At the same time, Potatoes planted perpendicular to the contour lines resulted in the lowest erosion rate, at only 114.51 tons/ha/year. Economic analysis, considering crop productivity and financial outcomes, revealed the highest productivity for potatoes planted perpendicular to the contour at Rp. 26.891 kg/ha, and the highest Income for the contour planting of potatoes at Rp. 215.133.360/ha. Optimization using the MOORA method, which calculates minimal erosion (cost) and maximal Income (benefit), yielded the highest value for potatoes planted along the contour at 0.409963. This was followed by perpendicular planting (0.075816) and shallots along the contour (0.067163). The MOORA method can provide optimal planting pattern recommendations by analyzing multiple criteria, including soil erosion and productivity, thereby offering practical guidance to farmers and policymakers in making more economically viable and sustainable planting decisions.